Ulysses and Mona [videorecording (DVD)] - Betbeder, Sébastien, 1975-; Cantona, Éric, 1966-; Dolmaire, Quentin; Issa, Manal (Film Movement series., 2019)
Ulysses, fifty-five years old, is a Contemporary artist. Four years ago, Ulysses ran away from his family and put an end to his career. Nowadays, he lives alone, with his dog Joseph, in an old manor in the middle of the forest. He spends his days playing tennis on his own against a pitching machine or listening to horror movies soundtracks. In short, Ulysses is bored to death, but he is too proud to admit it. Mona is twenty and is an arts student. Her life as an artist couldn't be more uneventful, between still, nude drawing workshops or theory classes, taught by geriatric teachers. Mona decides out of the blue to go and meet Ulysses. After a laborious first attempt and some misfortune, both of them will end up on a journey that will change their lives forever.